Effect of education level on delivery at home evidence from eastern Indonesia - Rohmah, Nikmatur; Laksono, Agung Dwi; Dewi, Sofia Rhosma (Alma Ata University Press, 2023)
Background: Eastern is an area that tends to be lagging in terms of health development in Indonesia, including delivery services. Objectives: The study aims to analyzes the effect of education level on delivery at home in eastern Indonesia. Methods: The study employed secondary data from the 2017 Indonesian Demographic and Health Survey (IDHS). The samples of this study were women of childbearing age, who labored in the last five years, and there were 2,299 respondents. Apart from education level as an exposure variable, the study used seven control variables, i.e., residence, age, employment, marital, parity, health insurance, and wealth status. In addition, the study employed binary logistic regression in the final stage. Results: The results inform women with primary education have a 1.520 times higher probability than women with higher education to deliver at home (AOR 1.520; 95% CI 1.520-1.521). Moreover, women with secondary education are 1.206 times more likely than women with higher education to deliver at home (AOR 1.206; 95% CI 1.206-1.207). Thus, the results of this analysis inform the lower the education level, the higher the possibility for delivery at home. Apart from education level, the study also found other control variables significantly related to maternal delivery at home in eastern Indonesia. Seven control variables are proven to be related to home delivery in Eastern Indonesia. The first lives in the countryside, the second is younger, the third does not work, the fourth has a partner, the fifth is multiparous, the sixth has no insurance, and the seventh is very poor. Conclusions: The study concluded that education level affects maternal delivery at home in eastern Indonesia.The recommendation from this research is the need for policies that can minimize the limitations of vulnerable groups in utilizing help in hospitals.